DESIGN ANALYSIS OF IMPRESSED CURRENT CATHODIC PROTECTION (ICCP) SYSTEM FOR UNDERWATER STRUCTURE OF INDONESIAN WARSHIP (KRI) - Arda Arda Widyaksa; Pompy Pratisna; Wawan Kusdiana; M. Yunus Abdullah (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
In carrying out these basic tasks the Navy relies heavily on the readiness of the Indonesian Warship (KRI),including the readiness of underwater construction in KRI from corrosion attack on sea water. Nowadays, KRIuses Sacrificial Anode Cathodic Protection (SACP) from corrosion attack. Whereas, SACP system has someweakness, such as the lifetime protection is short. The aim of this paper is to the analysis of Impressed CurrentCathodic Protection (ICCP) design of the underwater structure of KRI using computative theory calculation andspecimen test. The results of ICCP design showed that the specimens I required 0.081 Ampere (A) forprotection current, specimen 2 required 0.010 A for protection current, specimens 3 required 0.00251 A. Withpotential protection between -800 mV up to -1100 mV, it described that the ICCP system is reasonable. Theresult of cathodic protection design towards an underwater structure of KRI (TR-40 Type) showed that 1.75 forAmpere (A) and 3.35 volt DC for voltage. The benefit of this paper is a reference standard in the planning of theICCP design at KRI.Keywords: Corrosion, Underwater Structure of Warship, Impressed Current Cathodic Protection (ICCP).